Effective Strategy for Increase Awareness Culture Safety Among Workers: Analysis Literature - Wijayanto, Christiadi; Arifin, Antoni Ludfi (Dinasti Publisher, 2025)
Understanding to culture safety is element key in create a comfortable work area as well as productive. This research aiming For analyze efficient strategies in upgrade understanding culture safety in the group workers sourced from literature? previous. This study using the procedure analysis literature against 23 journals that reviewed aspect culture safety, attitude workers, as well as implementation system management safety in various industrial zones. The results of the analysis display when approach based on training, efficient communication, involvement? management, as well as implementation